Transfer of learning: Radiographers' perceptions of simulation-based educational intervention. Issue 3 (August 2016) - Aura, S.; Jordan, S.; Saano, S.; Tossavainen, K.; Turunen, H.
Abstract: Aim: The aims of this qualitative descriptive study were to 1) explore and define radiographers' competence in intravenous pharmacotherapy before and after a simulation-based education, 2) examine radiographer's perceptions of transfer of learning into clinical practice. Method: Sixteen diagnostic radiographers in one hospitals' Clinical Radiology Unit were individually interviewed before a multidisciplinary simulation-based pharmacotherapy education intervention in 2012 and fourteen were re-interviewed after the intervention 6–7 months later. Data were analyzed using qualitative content analysis. Results: Before education the participants reported uncertain competence in pain management during imaging procedures and acute situations. These weak competence areas identified were strengthened and self-confidence grew. The intervention improved the domains of pharmacotherapy-related patient safety; teamwork development and communication skills. In addition, the radiographers indicated that the iv. pharmacotherapy knowledge from simulation learning was transferred to routine work. Conclusion: The results of this study suggest simulation-based education is suitable for radiographers' pharmacotherapy learning. Adequate pain measurement and management are essential during invasive procedures and these skills can be realistically learned in simulations and transferred to clinical practice. Highlights: Simulation education is suitable for professionals' pharmacotherapy education. Radiographers felt education empowered them to manage acute situations. Skills in pain measurement, analgesia and patient monitoring enhanced. Communication and teamwork skills were enhanced. Simulation-based learning was transferred to clinical practice.